Content analysis of websites selling alcohol online in Australia. (9th January 2020) - Colbert, Stephanie; Thornton, Louise; Richmond, Robyn
Abstract: Introduction and Aims: Online alcohol sales have experienced rapid growth in Australia in recent years, averaging 14% annual growth over the last 5 years. This study aims to provide information about the advertised sales and delivery practices of online alcohol retailers in Australia and the potential implications for alcohol‐related harm. Design and Methods: A cross‐sectional website content analysis of the 65 most visited Australian alcohol delivery websites. Data extracted for content analysis from each of the included websites fell under six broad categories: product range; average prices; promotions and discounting; payment and delivery; age verification methods; and policy statements. Results: Online alcohol retailers offer a variety of alcohol products cheaply, with around 20% selling a 750 mL bottle of wine for under AUD$5. Most (81.5%) offered discounts for purchasing greater quantities and (89.2%) offered visitors an opportunity to sign up to receive discounts and promotions directly via email. Concerningly, 13.8% of websites allowed customers to purchase alcohol using a 'buy now, pay later' scheme such as AfterPay or Zip Pay. Delivery in under two hours was available from 12% of retailers. Most retailers (75.4%) advertised a willingness to leave alcohol unattended at an address. Discussion and Conclusions: Online alcohol retailers offer a variety of alcohol products cheaply, accompanied by heavy promotions and discounting. Most retailers advertise a willingness to leave alcohol unattended at an address without having verified the purchasers age, which raises concerns about access to minors. Improved regulation of this growing industry in Australia is required. [Colbert S, Thornton L, Richmond R. Content analysis of websites selling alcohol online in Australia. Drug Alcohol Rev 2020]